Character Education in The Quran and Its Relevance for Human Life - Khodijah, Siti (Proceeding International Conference on Religion, Science and Education, 2022)
The problem of character is a very important problem for the interaction of human life every day. In the Qur'an, character is identical with morality, as a result of the process of applying a solid faith in humans based on the Qur'an as a guide for human life. In the Qur'an, the commendable character (morals) of humans is a combination of the results of internalizing religious, ethical and moral values in a person which is characterized by good or positive attitudes and behavior. This study aims to describe character education in the Qur'an and its relevance to human life. This research is a type of library research, namely the method of collecting library data sourced from the Qur'an, books and journals about character education. The results of this study can be used as reading material to add information for readers and become a reference for humans in studying, understanding and implementing character education in everyday human life.